A Remark on Pál Type Interpolation on Non-Uniformly Distributed Nodes on the Unit Circle (Analysis in Theory and Applications, 2014)
In this paper we study the problem of explicit representation and convergenceof Pál type (0;1) interpolation and its converse, with some additional conditions,on the non-uniformly distributed nodes on the unit circle obtained by projecting theinterlaced zeros of $P_n(x)$ and $P′_n(x)$ on the unit circle. The motivation to this problemcan be traced to the recent studies on the regularity of Birkhoff interpolation and Páltype interpolations on non-uniformly distributed zeros on the unit circle.
Keywords: Pál type interpolation; non-uniformly distributed set of points on unit circle; Legendre polynomials.